PENGARUH PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN BROSUR TERHADAP HASIL BELAJAR IPA FISIKA SISWA KELAS VIII DI SMP PEMBANGUNAN LABORATORIUM UNP - Muhammad Yogi Rivano; Djusmaini Djamas; Ramli Ramli (Universitas Negeri Padang, 2018)
There are some things that cause low learning outcomes of students. Firstly, students are less involved in the learning process. Secondly, teachers are unable to accommodate all the needs of students. Thirdly, students are less interested in reading materials related to physics. The aims of this work is to determine the effect of the implementation of guided inquiry learning model using brochure on the results of physics learning class VIII on light material and optical devices. This research is a quasi-experimental design with randomized control group only design. The population was all 8th grade students in SMP Pembangunan Laboratorium UNP, academic year 2016/2017. The purposive sampling with cluster random sampling technique was used. The reseaarch instruments used in this study are result of final test to measure knowledge aspect, and perfomance assesment sheet to measure skill aspect. Data are analyzed by testing the equality of two average. The equality testing are done to both of aspects, knowledge and skill. The result showed the average value of learner at both classes are 85.16 and 78.28 for knowledge aspect, 85.46 and 80.56 for skill aspect. By t test, for both aspects, we got that t>ttable, it means the alternative hypothesis is accepted. By the descriptive data, we got that there are a significant influence from the model implementation.. We conclude that the guided inquiry learning model using brochures has a significant effect on the results of physics studies on lightweight and optical devices in the SMP Development Laboratory UNP.